Autoethnography as a research method: advantages, limitations and criticisms - Méndez, Mariza G. (Colombian Applied Linguistics Journal, 2013)
The aim of this article is to review the literature on autoethnography as a research method. It will first describe what is meant by autoethnography, or evocative narratives, and consider the particular features of this type of method. The paper will go on to explore the advantages, limitations and criticisms this research method has endured since its emergence during the 1980s. Finally, the different approaches to the evaluation of autoethnography will be reviewed.